2021
DOI: 10.3389/fpubh.2021.652610
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pets on Everyday Life for Older Adults During the COVID-19 Pandemic

Abstract: Purpose: The social and behavioral health of older adults is of particular concern during the COVID-19 pandemic. It is estimated that at least 50% of older adults in the U.S. have pets; while pets may be a source of support, they could also pose unique challenges during an already trying time. We aimed to investigate how pets impacted the everyday lives of older adults in the early stages of the COVID-19 pandemic.Methods: A large survey of U.S. pet owners (n = 2,068) was administered to assess the impact of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
4
52
0
Order By: Relevance
“…Their results indicated that for some of the survey participants, their cats can substitute for other humans in their social network [ 23 ]. In most cases, cats appear to be an additional source of emotional support [ 24 ], especially for those people who are strongly attached to their animals. Therefore, both social support and attachment are at work in these relationships, the relative importance of each depending upon the individual person in question.…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated that for some of the survey participants, their cats can substitute for other humans in their social network [ 23 ]. In most cases, cats appear to be an additional source of emotional support [ 24 ], especially for those people who are strongly attached to their animals. Therefore, both social support and attachment are at work in these relationships, the relative importance of each depending upon the individual person in question.…”
Section: Discussionmentioning
confidence: 99%
“…[24] also showed that those who frequently took their pet to work evidenced higher work-related quality of life, general well-being, home-work interface, job-career satisfaction, more control at work, and better perceived working conditions compared to those who never took their pet to work. An experimental study showed that the presence of a dog in a work group increased positive emotions and improved the social and emotional climate [26]. It is likely that these bonds positively impact workers' well-being, and at the same time, promote the creation of positive work environments [27,28].…”
Section: The Benefit Of Pet-friendly Practicesmentioning
confidence: 99%
“…Fears intensified as the number of cases grew exponentially and scientific knowledge of the means of transmission was limited and contradictory [2]. To mitigate the potential spread of COVID-19, numerous governmental agencies issued public health mandates requiring Research conducted during the initial months of COVID-19 has shown that while many companion animal guardians were worried about being able to provide for their companion animal and access veterinary medical services [48][49][50][51][52][53][54], they were grateful for the increased quality time with them and reflected on how their companion animal offered a decreased sense of loneliness [49,54,55]. Given the strong connections people have with their companion animals, and the potential benefits of companion dogs and cats, this study hypothesized that companion dogs and cats would positively impact guardians' mental health.…”
Section: Introductionmentioning
confidence: 99%